Analysis of the Decomposition of Energy Intensity in Tunisia - Ben Hammamia, Amira; Dakhlaoui, Ahlem; Abbassi, Abdessalem (International Journal of Energy Economics and Policy, 2014)
In this article, we are interested in the analysis of energy intensity by the Fisher Ideal Index method, a method belonging to the approach of the Index Decomposition Analysis (IDA), in order to highlight the effects which contribute to its reduction. The use of this method allowed us to decompose the variation of energy intensity in Tunisia for the period 1990-2008 into two effects: one effect due to the structural change of the economy and another arising from energy efficiency. We show that the effect of enhancing energy efficiency is the main contributor to the reduction of energy intensity in Tunisia. Indeed, the setting into action of the policy of energy control has improved energy efficiency by allowing reaching a lower level of energy intensity. On the other hand, the effect of structural change through the orientation of the Tunisian economy toward the tertiary sector has also helped to reduce the energy intensity. Keywords: energy intensity; energy efficiency; economic structure; Index Decomposition Analysis (IDA) JEL Classifications: C4; Q4